2019
DOI: 10.2147/prbm.s177834
|View full text |Cite
|
Sign up to set email alerts
|

<p>How do “selfies” impact adolescents’ well-being and body confidence? A narrative review</p>

Abstract: Social media use has grown rapidly in recent years, with one of the most popular activities for young people being the taking, sharing, and browsing of digital self-photos, known as selfies. However, research has only recently begun to investigate selfies, and little is known about selfie practices in adolescents, or the associations between these practices and well-being and body confidence. This paper aimed to address this gap and conduct a narrative review of selfie practices and the relationships with well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 60 publications
1
72
1
4
Order By: Relevance
“…Adolescence is a temporal frame during which physical changes and identity development occur, and teenagers acquire a greater awareness of the body, both their own and those of their peers ( 49 ). Posting pictures on social media is one of the most common practices among young people, especially self-photos (commonly known as “selfies”) ( 89 ). Exposing and being exposed massively to pictures of body might lead to negative outcomes, such as body image dissatisfaction, defined as “ the discrepancy between identification of one's own figure (actual) and the figure chosen as the desirable self-image ” ( 90 ), or alterations in nutrition habits, to the extent of the development of EDs.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Adolescence is a temporal frame during which physical changes and identity development occur, and teenagers acquire a greater awareness of the body, both their own and those of their peers ( 49 ). Posting pictures on social media is one of the most common practices among young people, especially self-photos (commonly known as “selfies”) ( 89 ). Exposing and being exposed massively to pictures of body might lead to negative outcomes, such as body image dissatisfaction, defined as “ the discrepancy between identification of one's own figure (actual) and the figure chosen as the desirable self-image ” ( 90 ), or alterations in nutrition habits, to the extent of the development of EDs.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…In the past 5 years, a growing number of social researchers have investigated how young people in the Global North use social media for health-related purposes. Analyses of the content of youth-oriented social media [ 20 - 22 ] and visual media, such as selfies [ 23 , 24 ] and the use of hashtags [ 25 , 26 ] as a way of organizing communities of young people around topics including fitness, sporting activities, health, diet, sexuality, gender identity, and self-care, have received attention in the literature. Researchers have demonstrated that social media influencers, microcelebrities, and other content creators, many of whom are young people themselves, are playing important roles in conveying health information and providing emotional support to young people [ 14 - 16 , 26 - 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, adolescents may interpret this feedback as their peers' evaluation of their physical appearance. A recent narrative review of studies examining adolescents' selfie practices found that adolescents' body image and feelings of self-worth were associated with how many "likes" they received on a photo (McLean et al, 2019). Although it did not focus on physical appearance specifically, an fMRI study provided evidence that receiving likes is associated with social reward:…”
Section: Biv Peer Approval Of One's Own Imagesmentioning
confidence: 99%